A Low Complexity Algorithm for Selective AF-OFDM System - Al-Tous, Hanan; Barhumi, Imad (IEEE VTS Vehicular Technology Conference (1999), 2014)
A low complexity algorithm is proposed for joint allocation of power profiles at the source and relay nodes and subcarrier assignment for single user amplify and forward (AF) cooperative communication using orthogonal frequency division multiplexing (OFDM) system. The relay uses AF cooperative relaying to transmit messages on a set of available subcarriers with diversity. The remaining subcarriers are used for direct transmission without diversity. The objective is to allocate the resources to maximize the sum rate subject to individual power constraint on each node. We formulate such a problem as subcarrier based resource allocation that seeks joint optimization of subcarrier assignment and power profiles at the source and relay nodes. The algorithm is based on an ordering of the channel gain's ratio and splitting them into two partitions, then searching for the partition that maximizes the sum rate. Simulation results demonstrate the merit of the proposed algorithm.